Cytokines reinstate NK cell–mediated cancer immunosurveillance - Zitvogel, Laurence (J Clin Invest, 2014)
In healthy individuals, cells that lose expression of MHC class I molecules are quickly targeted for elimination by NK lymphocytes. A paradox in cancer immunology is the observation that many tumor cells often have a drastic reduction of MHC class I molecules, yet these cells are not eliminated by NK cells, as they should be. In this issue of the JCI, Ardolino et al. demonstrate that NK cells that infiltrate MHC class I–deficient tumors acquire an anergic state that can be reversed by particular combinations of exogenous cytokines. These results indicate that IL-12 plus IL-18 or a recombinant interleukin engineered to stimulate the IL-2 receptor β/γ heterodimer (but not the IL-2 receptor α/β/γ complex) have the potential to be used clinically to reinstate immunosurveillance against MHC class I–deficient tumors.